Major Infrastructure Planning and Delivery Exploring Nationally Significant Infrastructure Projects (NSIPs) in England and Wales - Clifford, Ben (UCL Press, 2023)
Major Infrastructure Planning and Delivery introduces the system for planning and consenting Nationally Significant Infrastructure Projects (NSIPs) in England (which has also applied for some schemes in Wales). These are the major projects involving power stations and large renewable energy schemes, motorways, railways and a range of other high profile, high impact and sometimes controversial development schemes, including some closely linked to the UK's transition to net zero. The book explains where this separate system for governing major infrastructure came from and how it operates in practice, with a particular focus on the relationship between planning, consent and delivery of these infrastructure projects. Detailed case studies of the A14 highway, Thames Tideway super sewer, Galloper offshore windfarm and Progress Power station, drawing on research by the authors, illustrate issues of the often overlooked continuing role of local government, the engagement of local communities and stakeholders, and the modification of schemes between consent and construction. At a time of ongoing government planning reform, increased concern about climate change, and still unresolved consequences of Brexit, as well as timeless debates such as over national need versus local impact, this timely book offers rich detail on the particular approach to major infrastructure planning in England, but also speaks to wider issues around the governance of development and implementation of government policy under late capitalism.